Big data: what it can and cannot achieve. (6th June 2018) - Schofield, Peter; Das-Munshi, Jayati
SUMMARY: This article looks at the use of large datasets of health records, typically linked with other data sources, in mental health research. The most comprehensive examples of this kind of 'big data' are typically found in Scandinavian countries, although there are also many useful sources in the UK. There are a number of promising methodological innovations from studies using big data in UK mental health research, including: hybrid study designs, data linkage and enhanced study recruitment. It is, however, important to be aware of the limitations of research using big data, particularly the various pitfalls in analysis. We therefore caution against abandoning traditional research designs, and argue that other data sources are equally valuable and, ideally, research should incorporate data from a range of sources. LEARNING OBJECTIVES: Be aware of major big data resources relevant to mental health research Be aware of key advantages and innovative study designs using these data sources Understand the inherent limitations to studies reliant on big data alone DECLARATION OF INTEREST: None.